Da emergência ao presente da liberdade assistida: uma análise da governamentalidade de jovens infratores - Rodrigues, Ariane Wollenhoupt da Luz (2013)
The Statute of Children and Adolescents is characterized by protectionism, in order to claim and guarantee the rights of children and adolescents. In the Statute are stated the rights, the safety measures, the juridical measures in case of infractions against and by adolescents. The theme of this work refers to one of these elements, the social and educational measures, which aim at the teenagers who committed an offense (BRAZIL, 1990). Thus, the research object speaks about the Probation, as it occurs in an open environment and aims to monitor, assist and guide the young person who is in conflict with the law. The current study has sought an analyses of governmentality of this social and educational practice, and the problem was outlined as follows: how is the Probation as a governing practice for young offenders? It is possible to note that the socio educational measures, in general, have an intention to seek a government for young delinquents, to produce in them acceptable behaviors, as those highlighted in the objectives of Probation. To analyze the establishment of this governing practice a genealogical study was held, through the analysis of the speech of the laws which deal or have dealt with the problem of adolescent offenders. Thus, the starting point of this work is the early 20th century, with the institution of the first statutory law specifically to this audience, which was seen at the time as "minor . Next, it was analyzed the material relating to institutions and policies attending the young offenders, also seeking to understand the not discursive practices, among them, those made by the Assistance Service to Minors, and the National Foundation of Welfare for Minors during the military dictatorship. Such texts and policies subsidize legislative changes regarding the Code of Minors of 1979 and the establishment of the Statute of Children and Adolescent, from 1990. In this sense, it was believed on the hypothesis of the existence of at least four logics about the measures: the punishing, educational/resocializing, human rights / guarantee and actuarial, which have had moments of stress and abrasion. The results have showed that, during most of the 20th century, the predominance of a logic of punishment is supported by a resocializing speech, aiming at the young offender an indefinite segregation. It was concluded that, in Probation, self-reformation logic/guarantee, it was applied as management and punishing, as long as it selects medium risk offenders to the population, by means of a measure considered less constraining, but still punishing.